Self-regulating microbiome networks ensure functional resilience of biofilms in sand biofilters during manganese load fluctuations. (1st January 2021) - Zhao, Xin; Yang, Yang; Feng, Kun; Wang, Xiuheng; Liu, Bingfeng; Xie, Guojun; Xing, Defeng
Highlights: Local Mn(II) concentration influences microbiome assembly in sand biofilters (SBFs). Biofilm microbiome self-regulates and maintains functional resilience in SBFs. The complexity of interspecies interactions of SBFs changed with depth. Low-abundance keystone species can have major roles in ecosystem function. Biofilms responded to manganese load increases by altering the ecological network. Abstract: Sand biofilters (SBFs) are commonly used to remove manganese (Mn(II)) from drinking water. Mn(II) load variation frequently occurs in SBFs due to fluctuating influent Mn(II) concentrations or flow rates. Therefore, it is important to understand the responses of microbial biofilms in SBFs to environmental disturbances and how they affect Mn(II) oxidation efficiency. Here, the responses of microbial ecological networks and Mn(II) removal in SBFs to increasing Mn(II) load were investigated. The Mn(II) removal efficiency in two SBFs remained at 99.8% despite an increase in influent Mn(II) from 2 mg/L to 4 mg/L, but significantly deteriorated (50.1–58.5%) upon increasing the filtration rate. A canonical correlation analysis of the microbial communities indicated that the local Mn(II) concentration and biofilter depth impacted community compositions of biofilms. The dominant species within the biofilms exhibited clear stratification, with simple associations in the upper layer of the SBFs and more complex interspecies interactions in the bottom layers. Putative manganese-oxidizing bacteria Hyphomicrobium and Pedomicrobium dominated the microbiomes in different layers of SBFs, and changed relatively little in abundance when Mn(II) and filtration rate increased. The community networks showed that biofilm microbiomes in SBFs were resilient to the disturbance of Mn(II) load, primarily via regulating microbial interactions. High manganese loads negatively affected the functional modules for Mn(II) removal. Furthermore, the relatively rare species Candidatus Entotheonella palauensis was identified as a module hub, implying taxa with low abundances can have important roles in ecosystem function. These results shed new light on the ecological rules guiding responses of microbiomes in sand biofilters to environmental stress. Graphical abstract: Image, graphical abstract